Effects of cooling during cycling on physiological and cognitive responses - Brandenburg, J. P.; Gaetz, M. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction Cooling strategies applied during exercise often result in improved performance. The effect of these strategies on cognitive and brain function remains unclear. This study examined the effects of cooling on physiological and perceptual responses, cognitive function, and the electroencephalogram (EEG) during vigorous cycling. Methods: Nine active males (21 ± 3 y; 76.9 ± 7.7 kg; 179.6 ± 3.8 cm) completed two trials in a randomized order: a control (CTL) and a cooling (COOL) trial. In each trial, subjects performed 30 min of cycling at a constant power output (2.4 ± 0.2 W/kg). During COOL, subjects wore a cooling vest, cooling collar, and received fan cooling while cycling. No cooling was provided in CTL. Heart rate (HR), core (TC) and tympanic (TTY) temperatures, thermal sensation (ThS), and RPE were measured throughout. Cognitive function was measured using the Stroop test and EEG. In both trials water was ingested at a rate to match sweat losses. Air temperature (~23°C) and humidity (~50%) were similar in both trials. Results: The maximum attained HR was lower in CTL (166 ± 15 b/min) than in COOL (161 ± 14 b•min-1) (p=0.005). TC rose by 1.1 ± 0.3°C to a high of 38.3 ± 0.4°C in CTL and by 0.9 ± 0.2°C to peak at 38.2 ± 0.4°C in COOL (no difference). The rise in TTY was larger in CTL (1.1 ± 0.3°C) than in COOL (0.8 ± 0.3°C) (p=0.018). ThS was lower throughout COOL (p<0.001) while there were no differences in RPE. No significant changes were observed for the Stroop reaction time and errors in the CTL and COOL trials. In CTL, but not COOL, the number of Stroop errors immediately post-cycling was significantly correlated with the rise in TTY (r2=0.59; p=0.025) and the rise in TC (r2=0.78; p=0.004). During cycling differences between CTL and COOL in EEG ratios of low/higher frequency EEG bandwidths emerged (e.g. Theta/Beta1 ratio, p=0.019). Significant correlations were observed between EEG ratios and the number of Stroop errors (e.g. ratio of alpha/beta1 activity vs. Stroop errors; r2=0.63; p=0.01). Discussion: Cooling, during 30 minutes of cycling, moderated the cardiovascular, thermal, and perceptual responses, the increase in low/higher frequency EEG ratios, but did not produce differences in Stroop test variables. Generally, the increase in low/higher frequency ratios during cycling reflects a neural state that is sub-optimal for cognitive functioning (e.g. increased theta, decreased beta activity). The significant correlations between the low/higher frequency EEG ratios and number of Stroop errors support this interpretation. It may be the case that increases in body temperature, as seen with TC and TTY, lead to the changes in the EEG and cognitive functioning. The significant relationships between the number of Stroop errors and the increases in TTY and TC support this observation.